PREVALENCE OF INTESTINAL PARASITES IN CATTLE SLAUGHTERED IN ABA - F. U, Okike-Osisiogu; G, Arinze Adibelem; U, Ekaiko Marshall (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
A study on the prevalence of gastrointestinal parasites of cattle was carried in ogbor hill, Aba, Abia state. Of the 135 fecal samples examined, 68 male and 67 female cattle, 118(87.41%) was infected with at least one intestinal parasites. Ascaris spp was more prevalent 27.97% followed by Monezie 19.49%, Bonostomum 16.10%, Trichuris14.41%, Strongyliod 13.56% and Toxocara spp 8.48% respectively. The study reveals that there is a high tendency for increase in the transmission of helminth zoonoses within the studied area. But with personal hygiene and environmental sanitation, the prevalence of helminthic diseases can be reduced.